Analysis of BPJS Employment Membership for Informal Sector Workers in Medan City (Case Study of BPJS Employment, North Medan Branch) - Diana Diana; Wahyu Syarvina (Penerbit Jurnal Indonesia, 2022)
Every worker has the right to work safety protection for both formal and informal workers, it is conceivable if the workers do not have social security and this has an effect on weakening protection for workers and for sure poor employee performance. So the government must improve and increase social security for non-wage workers, because there are still many informal workers who do not use BPJS Employment. As we know BPJS Ketenagakerjaan is a public legal entity that has responsibility to the president and has the function to organize programs Work Accident Insurance (JKK), Death Security (JKM), Old Age Security (JHT) and Pension Security (JP) for all Indonesian workers and including immigrants who work in Indonesia for 6 months of work. What if there are informal workers who do not participate in the program, it can be said that workers in Indonesia are not yet fully prosperous. The purpose of this study is to find out why BPJS Employment participation is still low in the city of Medan and how BPJS Employment increases participation for informal sector workers . This study uses a qualitative method by presenting an overview of this problem.